Debreceni Református Kollégium teológiai oktatásának története 1850–1912. A Teológiai Akadémia a Kollégium oktatási rendszerében - Kovács, Ábrahám (Gerundium, 2018)
The History of Theological Education at Debrecen Reformed College between 1850 and 1912. The changes in the educational system of Theology at Reformed College of Debrecen were heavily influenced by the political-social events of historic Hungary between 1850 and 1912. The first date signals the introduction of arbitrary rule of the Habsburg monarch who suppressed the Hungarians during the War of Independence in 1848-49. The closing date is the emergence of a new state run university in Debrecen. The study throws light on how the Organisations Entwurf tried to modernize as well as Germanize the education system in the Habsburg Empire. As a result, the traditional education structure at the College was entirely restructured. It brought about the disintegration of humanity and art faculty into a grammar school thereby only the law and theological faculties were left intact for a while. The Reformed Church District strongly protested against the dismantling its more than 300 years old education system. It is the irony of history what the oppressing Austrian could not achieve, it was realized after the Compromise by József Eötvös, the Hungarian minister of culture, religion and education. Needless to say that education at all levels needed to be modernized and standardized. It is clear that it had a positive impact on the curricula of Reformed theological education in the long run. The paper introduces briefly the life of theological professors, their career with a view to their studies abroad and finally their works at various departments of theology.